Return to the motherland: Russian migrants in hockey's changing world system - Cook, Paul Richard (University of Ottawa (Canada), 2009)
Since 2000, Russian players are increasingly absent from the National Hockey League. This project explores the relationship between changes in the political economy of Russian hockey and the factors that shape the migratory decisions of Russian players. In using Wallerstein's World Systems Theory, it is argued that specific events relating to a nation's place within an economic and/or cultural relationship can significantly alter patterns of migration. Russia's newfound economic strength and confidence on the world stage is evident in the support for the country's new Kontinental Hockey League. The resulting changes in the political economy of Russian hockey, coupled with the restrictive nature of the National Hockey League's salary cap have led to a tremendous decrease in the number of Russian players in the NHL.
Keywords: Sociology, Theory and Methods.; Business Administration, Sports Management.; Slavic Studies.